ANALISIS PENGARUH PERFORMANCE LOW TEMPERATURE ECONOMIZER TERHADAP EFISIENSI BOILER 1000 MW DAN BIAYA PRODUKSI PLTU DI SERANG - Parwitasari, Fadella Binda; Luthfie, Alief Avicenna (Universitas Mercu Buana, 2023)
Low Temperature Economizer (LTE) is a support system for boilers with a capacity of 1000 MW at unit 1 PLTU in Serang which serves to increase the temperature of the feed water by utilizing the heat from the exhaust gases. In 2021, LTE in boiler unit 1 experienced a disruption so that LTE had to stop operating. This has an impact on boiler efficiency and production costs at unit 1 PLTU in Serang, especially on fuel costs. This research was carried out by collecting data on DCS and collecting data in the field, then data processing was carried out. The efficiency calculation method used is direct efficiency calculation, with boiler data retrieval when LTE leaks occur so that LTE stops operating compared to boiler operating conditions with LTE after repair. The coal used is lignite type coal which has a calorific value below 4500 kCal. Boiler efficiency when LTE stops is only 76.04%. This value is smaller than when the boiler operates with LTE which reaches 85.12%. The repair of LTE pipeline leaks can save coal usage by more than 4 tons per hour. Production costs on the use of coal can be reduced to more than Rp. 80,000,000 per day.Keywords: Low Temperature Economizer, Boiler Efficiency, Production Cost